Is 'everything everywhere'? Unprecedented cryptic diversity in the cosmopolitan flatworm Gyratrix hermaphroditus. (27th July 2021) - Tessens, Bart; Monnens, Marlies; Backeljau, Thierry; Jordaens, Kurt; Van Steenkiste, Niels; Breman, Floris C.; Smeets, Karen; Artois, Tom
Abstract: Many nominal species of microscopic animals traditionally fitting the 'everything is everywhere' paradigm have been revealed to be complexes of cryptic species. Here, we explore species diversity within the micrometazoan flatworm Gyratrix hermaphroditus —unique among meiofauna because of its global occurrence in a wide variety of brackish, freshwater and marine environments. With maximum likelihood and Bayesian approaches, we analysed 18S, 28S, 5.8S and ITS2 rDNA sequences from 401 specimens across the global distribution of G. hermaphroditus . Generalized Mixed Yule Coalescent (GMYC) and Automatic Barcode Gap Discovery (ABGD) methods delineated 78 and 62 putative species, respectively. This renders G. hermaphroditus one of the most species‐rich complexes known to date. Based on shape variations of the male copulatory organ, 14 morphotypes corresponding with molecular clades were identified within the species complex. Within morphotypes, morphometric measurements were able to further discriminate between GMYC species using discriminant analyses. While most putative species occur on local or regional scales, over 10% are distributed over vast distances (>500 km apart) and two GMYC and six ABGD species have colonised multiple continents. This suggests that the cosmopolitanism of the G. hermaphroditus species complex is not just caused by mixing cryptic species with a more limited geographic distribution, but is due to the presence of previously unrecognised cosmopolitan taxa. The wide variation in distribution patterns between putative species indicates that meiofaunal biogeography should not be simplified into 'everything is everywhere', but rather entails every ecological state, extending from local endemism to true cosmopolitanism.